One-stage (Warsaw) and two-stage (Oslo) repair of unilateral cleft lip and palate: Craniofacial outcomes. Issue 7 (September 2015) - Fudalej, Piotr Stanislaw; Wegrodzka, Ewa; Semb, Gunvor; Hortis-Dzierzbicka, Maria
Abstract The aim of this study was to compare facial development in subjects with complete unilateral cleft lip and palate (CUCLP) treated with two different surgical protocols. Lateral cephalometric radiographs of 61 patients (42 boys, 19 girls; mean age, 10.9 years; SD, 1) treated consecutively in Warsaw with one-stage repair and 61 age-matched and sex-matched patients treated in Oslo with two-stage surgery were selected to evaluate craniofacial morphology. On each radiograph 13 angular and two ratio variables were measured in order to describe hard and soft tissues of the facial region. The analysis showed that differences between the groups were limited to hard tissues – the maxillary prominence in subjects from the Warsaw group was decreased by almost 4° in comparison with the Oslo group (sella-nasion-A-point (SNA) = 75.3° and 79.1°, respectively) and maxillo-mandibular morphology was less favorable in the Warsaw group than the Oslo group (ANB angle = 0.8° and 2.8°, respectively). The soft tissue contour was comparable in both groups. In conclusion, inter-group differences suggest a more favorable outcome in the Oslo group. However, the distinctiveness of facial morphology in background populations (ie, in Poles and Norwegians) could have contributed to the observed results.